2010
DOI: 10.1097/hjh.0b013e32833b1ee7
|View full text |Cite
|
Sign up to set email alerts
|

Healthy middle-aged individuals are vulnerable to cognitive deficits as a result of increased arterial stiffness

Abstract: It was concluded that healthy middle-aged adults are vulnerable to memory deficits as a result of normal increases in pulse pressure associated with ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 33 publications
5
47
1
1
Order By: Relevance
“…Psychological effects measured in terms of VAS score were not significant in our study for any aroma, whereas positive psychological effects are reported in the past with Chocolate [3,4], Green tea [5,6], Apple [7], and Chamomile [12,13]. Chamomile which demonstrated no any significant physiological effect in our study, is reported to have stabilized blood pressure [13] and reduced pulse [14].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Psychological effects measured in terms of VAS score were not significant in our study for any aroma, whereas positive psychological effects are reported in the past with Chocolate [3,4], Green tea [5,6], Apple [7], and Chamomile [12,13]. Chamomile which demonstrated no any significant physiological effect in our study, is reported to have stabilized blood pressure [13] and reduced pulse [14].…”
Section: Discussioncontrasting
confidence: 57%
“…Strawberry is reported to have reduced nausea and vomiting [1], and ginger has led to pain relief [2]. Chocolate improved relaxation [3,4] and shaded white tea demonstrated improved task performance and enhanced positive mood [5,6]. With regard to the physiological impacts, reduced EEG theta activity with apple [7], reduced sympathetic nervous system (SNS) activity and increased in parasympathetic nervous system (PNS) activity with cedarwood [8], and decreased stress-related hormones with musk [9,10] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,[21][22][23][24] Consistent with these structural abnormalities, several studies have also shown PWV and CPP to be associated with cognitive function, including poorer memory and a worse performance on executive function tests. 10,11,[24][25][26][27] Much of the literature reflects cross-sectional studies, however, with fewer reports on the influence of arterial stiffness on neurovascular disease over time.…”
Section: Methods Study Participants the Framingham Heartmentioning
confidence: 99%
“…Brain lesions, such as ischemic lesions and white matter abnormalities resulting from augmented pressure, are thought to cause cognitive decline, thereby leading to dementia 24) . The augmented pressure caused by arterial stiffness independently predicts cognitive performance 25) , and many previously published studies evaluating the and pre-MMSE showed a significant difference in the changes in the post-MMSE scores between the normal and AS groups (F 5.95, p 0.02) (Fig. 1), indicating that elderly individuals with a higher degree of arterial stiffness may experience greater levels of cognitive decline, even after adjusting for age, BMI, gender and the pre-MMSE score.…”
Section: Mmsementioning
confidence: 99%